(3GdCefjI aj EOQGc GdefjIs - (3CHhGdYHGS TgGH GdOjf CMeO Hf GOQjS Hf YHO GdQMef GdUfgGLj GdbQGaj GdeGdcj,J (B684 (3g` s
(3ChdgG (B:s
(3CeG HYO ajbhd GdTjN TgGH GdOjf CMeO Hf EOQjS GdeGdcj Ef GdHGYK Ydi gPG GdcJGH eHGMK hbYJ ddaVdGA s
(3BNQgG (B:s
(3hEPG NQLJ GdaQhY GdcKjQI Ydi bGYOI hGMOI hgPG BNQ eG CQOJg ef cJGH GdCefjI aj EOQGc GdefjI s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B94 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B158s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B1 - (3U (B127s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3abg eGdc (B369) s
Keywords: (3Gdabg GdeGdcjs